1981
DOI: 10.1002/cyto.990010409
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric expression of differentiation in fine‐needle biopsies of breast cancer

Abstract: An automated method of particle sizing in fine-needle biopsies of human breast carcinomas is described. The average sue of clusters of cells aspirated from breast carcinomas was strongly correlated with cytologic differentiation of the tumors and also with the recurrence rate 3 years after mastectomy so that smaller cluster size w a s associated with poor differentiation and a poor prognostic outcome. It thus seems possible to express in quantitative terms the degree of differentiation of breast carcinomas. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Reproducibility among several observers was extremely high. Other investigators have reported similar results using morphometric methods (107,108). We believe that such quantitative methods of grading tumors will assume increasing importance in the future because of their precision and reproducibility.…”
Section: Tumor Differentiationsupporting
confidence: 50%
“…Reproducibility among several observers was extremely high. Other investigators have reported similar results using morphometric methods (107,108). We believe that such quantitative methods of grading tumors will assume increasing importance in the future because of their precision and reproducibility.…”
Section: Tumor Differentiationsupporting
confidence: 50%
“…In clinical cytology, cellular dissociation, with intact, single lying neoplastic cells is one of a number of features associated with malignancy. Previous studies have demonstrated that regional and distant metastases as well as local recurrence correlate with decreased cellular cohesion 15–18 . A dysfunctional, intercellular adhesion system may be responsible for the tumour cell dispersion pattern seen on fine needle aspiration cytology (FNAC).…”
Section: Introductionmentioning
confidence: 99%
“…11 The overall size of the cluster has previously been suggested to be a factor influencing prognosis. 14 In that study, malignancy correlated with the complexity in cyto configuration, in which the overall cell shape was related to the strength of intercellular cohesion. Important factors indicative of malignancy, such as cell overlap, cell adhesion, and irregular nucleus shape, are clearly expressed in this present study, according to the observed cluster shape.…”
Section: Discussionmentioning
confidence: 89%